Variabilidade genética em espécies de plantas do cerrado: uma avaliação cienciométrica e meta-analítica - Souza, Ueric José Borges de (2014)
The Cerrado biome of Brazil originally occupied approximately 2 million km2 of the country. It is formed by a heterogeneous mosaic of distinct habitats and has the richest flora of the savanas of the world, with high diversity at level of genera and families. It is also currently classified as a priority for conservation because of its rich biodiversity and simultaneous high level on threat due to the destruction of natural habitats resulting from anthropogenic activities. The advent of molecular biology techniques has allowed direct access to the genetic variability of species and populations and made it possible to infer the genetic variability within and among populations, increasing the interest in studying genetic diversity and structure in plant species population of the Cerrado biome. It was conducted here an exhaustive survey of scientific platforms such as the Web of Science, Scopus, Scielo and Google Scholar, to carry out an analysis of published papers evaluating the genetic variability within and among populations in plant species from the Cerrado biome, and to quantify and describe aspects of scientific production in the field of population genetics to plant species from the Cerrado using a scientometric approach, and using a meta-analytic approach to evaluate genetic variability, it was collected some of the genetic parameters estimated in the studies (observed (HO) and expected (HE) heterozygosities and the F statistics of Wright (FIS; FST or analogs)) to test the effect of this genetic parameters in some life history and ecological traits of the species and in methodological characteristics of the article. It was obtained 176 publications from 45 journals through the period of 1999-2012 and the number of studies published has increased significantly through this period. The journal “Genetics and Molecular Research” published the highest number of papers. Ninety-six species from 32 plant families were studied, with highest numbers from the family Fabaceae. Although the species comprised a wide sample of plants with different characteristics, trees, shrubs and herbs were the main life forms and “Mata de galeria”, “cerrado” and “cerradão” were the main fitofisionomies studied. The molecular markers used included microsatellites, cpDNA, isoenzymes, RAPDs, AFLPs and ISSRs and the Microsatellites were the most popular marker used and also show the highest mean value from the genetic variability within populations when compared across studies. It was observed that population genetics parameters molecular derived from molecular markers are closely associated with some life history traits and ecological traits of the species and with methodological characteristics of the article. The analyses allows a better understanding of the current knowledge on plant population genetics in Cerrado biome and the association with the population genetics parameters and some ecological, life history and methodological traits has considerable importance and may be useful to guide future research programs in this system with potential to produce information with important implications in evolutionary biology and ecology as well as in conservation biology